Necessary conditions for continuous-time optimization under the Mangasarian–Fromovitz constraint qualification - do Monte, Moisés Rodrigues Cirilo [UNESP]; de Oliveira, Valeriano Antunes [UNESP] (Taylor & Francis, 2019)
In this paper, a Mangasarian–Fromovitz-type regularity condition is presented with the purpose of obtaining first order necessary optimality conditions for continuous-time nonlinear programming problems with both equality and inequality constraints. The Karush–Kuhn–Tucker-type optimality conditions are obtained by means of geometric ideas, where a theorem of the alternative and a uniform implicit function theorem are the main tools.
Keywords: 90C30; 90C46; constraint qualifications; Continuous-time programming; Mangasarian–Fromovitz conditions; necessary conditions